Early immune response against Fonsecaea pedrosoi requires Dectin-2-mediated Th17 activity, whereas Th1 response, aided by Treg cells, is crucial for fungal clearance in later stage of experimental chromoblastomycosis - Siqueira, Isaque Medeiros (2020)
Chromoblastomycosis (CBM) is a chronic worldwide subcutaneous mycosis, caused by several dimorphic, pigmented dematiaceous fungi. It is difficult to treat patients with the disease, mainly because of its recalcitrant nature. The correct activation of host immune response is critical to avoid fungal persistence in the tissue and disease chronification. CD4+ T cells are crucial for the development of protective immunity to F. pedrosoi infection. Here, we investigated T helper cell response dynamics during experimental CBM. Following footpad injection with F. pedrosoi hyphae and conidia, T cells were skewed towards a Th17 and Th1 phenotype. The Th17 population was the main Th cell subset found in the infected area during the early stages of experimental murine CBM, followed by Th1 predominance in the later stages, coinciding with the remission phase of the disease in this experimental model. Depletion of CD25+ cells, which leads to a reduction of Treg cells in the draining lymph node, resulted in decline in fungal burden after 14 days of infection. However, fungal cells were not cleared in the later stages of the disease, prolonging CBM clinical features in those animals. IL-17A and IFN-γ neutralization hindered fungal cell elimination in the course of the disease. Similarly, in dectin-2 KO animals, Th17 contraction in the course of experimental CBM was accompanied by fungal burden decrease in the first 14 days of infection, although it did not affect disease resolution. In this study, we gained insight into T helper subsets’ dynamics following footpad injections of F. pedrosoi propagules and uncovered their contribution to disease resolution. The Th17 population proved to be important in eliminating fungal cells in the early stages of infection. The Th1 population, in turn, closely assisted by Treg cells, proved to be relevant not only in the elimination of fungal cells at the beginning of infection but also essential for their complete elimination in later stages of the disease in a mouse experimental model of CBM.